Analisis Profitabilitas Diferensiasi Produk Terasi Udang Padat dan Bubuk Instan - Nur, Hartatia; Indarsyih, Yusna; Budi, Nuryamin; Dwiyanty, Made (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2017)
The purpose of this research is to analyze the profitability of product differentiation of shrimp paste solid and instant powder. This research was conducted in April 2017 at the processing business of shrimp paste in Lampopala Village. The data source of this research is primary data and use data analysis of net income of business. The result of the research shows that the processing business of shrimp paste in one production for differentiation of solid shrimp paste product gives greater profitability than shrimp paste shrimp paste product for business actor with the gross margin difference of Rp88.400 / month and net income of Rp65.855 / month due to differences in the cash cost component used.